Global Research Alliance N2O chamber methodology guidelines: Guidelines for gap‐filling missing measurements. Issue 5 (15th September 2020) - Dorich, Christopher D.; De Rosa, Daniele; Barton, Louise; Grace, Peter; Rowlings, David; Migliorati, Massimiliano De Antoni; Wagner‐Riddle, Claudia; Key, Cameron; Wang, Daqi; Fehr, Benjamin; Conant, Richard T
Abstract: Nitrous oxide (N2 O) is a potent greenhouse gas that is primarily emitted from agriculture. Sampling limitations have generally resulted in discontinuous N2 O observations over the course of any given year. The status quo for interpolating between sampling points has been to use a simple linear interpolation. This can be problematic with N2 O emissions, since they are highly variable and sampling bias around these peak emission periods can have dramatic impacts on cumulative emissions. Here, we outline five gap‐filling practices: linear interpolation, generalized additive models (GAMs), autoregressive integrated moving average (ARIMA), random forest (RF), and neural networks (NNs) that have been used for gap‐filling soil N2 O emissions. To facilitate the use of improved gap‐filling methods, we describe the five methods and then provide strengths and challenges or weaknesses of each method so that model selection can be improved. We then outline a protocol that details data organization and selection, splitting of data into training and testing datasets, building and testing models, and reporting results. Use of advanced gap‐filling methods within a standardized protocol is likely to increase transparency, improve emission estimates, reduce uncertainty, and increase capacity to quantify the impact of mitigation practices.